OPTIMALIZATION NATIONAL TEXTILE FACTORY TO SUPPORT INDONESIAN NAVY SUPPLY CLASS II - Pribadi, Endik Kukuh; Soediantono, Dwi (Journal of Industrial Engineering & Management Research, 2022)
The Navy in carrying out their duties requires various supplies. One of these supplies is class II supplies, one of which is uniforms. The support for uniform supplies so far has not been optimal in terms of materials and availability throughout Indonesia. Indonesia has a large-scale national textile factory. The textile factory community was analyzed using the SWOT method for its role in supporting class II supplies. The results of the SWOT analysis of the national textile factory are in the 4th quadrant which supports the WT (weakness-threat) defensive strategy.